Human Resource Development at the University of Maribor – An Encouraging Working Environment - Žnidaršič, Jasmina; Tancer Verboten, Mojca; Bernik, Mojca (50 let Univerze v Mariboru: Pol stoletja znanja in raziskovanja, 2026)
The chapter focuses on staff development at the University of Maribor (UM), which is crucial for achieving academic, research, and organizational excellence. Since its establishment in 1975, the University of Maribor has systematically professionalized its employees, including academic, research, and non-pedagogical professional staff. Staff development has been adapted to societal needs, reflected in the introduction of new pedagogical approaches, digital technologies, and the Bologna study system. The analysis of the 2004–2023 period shows fluctuations in the number of employees, peaking in 2023 with 2,093 staff members. There is a noticeable trend of growth in research and teaching staff with higher academic titles and the professionalization of the workforce, especially in higher pay grades within groups H and J. The UM Strategy 2021–2030 (Univerza v Mariboru, 2021b) emphasizes the importance of interpersonal relations, work-life balance, and continuous skills development through programmes such as “Enhance UM.” The paper concludes that UM follows modern trends in digitalization, innovation, and lifelong learning, contributing to the development of its staff and society as a whole.